2015
DOI: 10.1128/aem.03950-14
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Stability of the Microbial Community in Sewage-Polluted Seawater Exposed to Natural Sunlight Cycles and Marine Microbiota

Abstract: Billions of gallons of untreated wastewater enter the coastal ocean each year. Once sewage microorganisms are in the marine environment, they are exposed to environmental stressors, such as sunlight and predation. Previous research has investigated the fate of individual sewage microorganisms in seawater but not the entire sewage microbial community. The present study used next-generation sequencing (NGS) to examine how the microbial community in sewage-impacted seawater changes over 48 h when exposed to natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…This method has been successfully applied to a detailed analysis of the human and animal microbiome as well as environmental samples, e.g. soil and seawater [911]. Since this method allows to obtain knowledge about all bacteria present in the sample, we can ask: (1) what bacteria exist in the blood of patients with clinical symptoms of SIRS (systemic inflammatory response syndrome), which have not been detected by available diagnostic methods and (2) whether any bacterial DNA is present in the blood of healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been successfully applied to a detailed analysis of the human and animal microbiome as well as environmental samples, e.g. soil and seawater [911]. Since this method allows to obtain knowledge about all bacteria present in the sample, we can ask: (1) what bacteria exist in the blood of patients with clinical symptoms of SIRS (systemic inflammatory response syndrome), which have not been detected by available diagnostic methods and (2) whether any bacterial DNA is present in the blood of healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…106,238,285 Thus, the overall effect of sunlight on bacterial communities in surface waters is the sum of detrimental and benecial processes. Advances in next-generation sequencing (NGS) technologies are making it cheaper, easier and faster to investigate bacterial communities in surface waters.…”
Section: Solar Radiation and Microbial Ecologymentioning
confidence: 99%
“…Advances in next-generation sequencing (NGS) technologies are making it cheaper, easier and faster to investigate bacterial communities in surface waters. Understanding the effect of sunlight on bacterial communities will be especially important when analyzing experimental ndings 238 and building models describing photo-induced chemical and biological processes affecting bacterial communities in aquatic environments.…”
Section: Solar Radiation and Microbial Ecologymentioning
confidence: 99%
“…The rapid decreasing (around 2-3 orders of magnitude) could be derived from both dilution and cell decay. A recent study showed the strong bactericidal effects of sunlight for sewage microbiota in seawater (Sassoubre et al 2015). Salinity could be another significant factor causing decay of the bacteria in the effluents (Anderson et al 2005).…”
Section: Fate Of Typical Effluent Bacterial Populations In Seawatermentioning
confidence: 99%